2019
DOI: 10.1002/ijc.32397
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and cancer incidence and mortality risk depending on family history of cancer in two prospective cohorts

Abstract: The extent to which a favorable lifestyle may lower cancer risk in subjects with a family history of cancer is unknown. We conducted a prospective study in two Swedish cohorts, the Malmö Diet and Cancer Study (MDCS; n = 25,604) and the Malmö Preventive Project (MPP; n = 16,216). The association between a favorable lifestyle (based on nonsmoking, normal weight, absence of excessive drinking, regular physical activity and healthy diet) and cancer incidence and mortality risk was assessed using Cox regression str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…It is worth noting that cancer patients belonging to lower socio-economic classes tend to have low screening rates worldwide; low rates have been reported for cervical cancer screening in China (Bao et al, 2018), prostate cancer in Switzerland (Guessous et al, 2016), breast cancer screening in different races in the United States (Singh and Jemal, 2017;Elewonibi et al, 2018), and breast cancer screening in Kurdish women in Iran (Aminisani et al, 2016). According to previous studies, the incidence rate of cancer, especially in low-resource countries (LRCs), is influenced by demographic transitions, changing disease patterns, unhealthy lifestyles, and community behaviour (Drake et al, 2020). Further, the mortality rate of cancer is higher in LRCs than in developed countries (Ghoncheh and Salehiniya, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that cancer patients belonging to lower socio-economic classes tend to have low screening rates worldwide; low rates have been reported for cervical cancer screening in China (Bao et al, 2018), prostate cancer in Switzerland (Guessous et al, 2016), breast cancer screening in different races in the United States (Singh and Jemal, 2017;Elewonibi et al, 2018), and breast cancer screening in Kurdish women in Iran (Aminisani et al, 2016). According to previous studies, the incidence rate of cancer, especially in low-resource countries (LRCs), is influenced by demographic transitions, changing disease patterns, unhealthy lifestyles, and community behaviour (Drake et al, 2020). Further, the mortality rate of cancer is higher in LRCs than in developed countries (Ghoncheh and Salehiniya, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A final and important explanation is non-occupational risk factors. Incidence of and mortality from all-site cancer is directly related to family history and unhealthy lifestyles 36 ; mortality is indirectly related to socioeconomic status. 37 In terms of their genetic, behavioral, and socioeconomic profiles, we suspect that fighter aviators are quite dissimilar than their peers in the general population and largely similar to their peers in the US Air Force officer population.…”
Section: Discussionmentioning
confidence: 99%
“…Debate exists as to how this impact occurs. In contrast, some previous studies have shown favorable outcomes for FHC-positive patients with the suggestion that those with positive FHC tend to seek health-related behavioral changes, including regular physical activity and tobacco/alcohol cessation, resulting in improved survival outcomes (Drake et al, 2020;Townsend et al, 2013). On the contrary, the disease stage at the time of diagnosis has been considered one of the most important factors in prognosis (Guneri & Epstein, 2014).…”
Section: Discussionmentioning
confidence: 93%